2020
DOI: 10.5006/3513
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Understanding the Origins of Excellent Corrosion Resistance in Metallic Alloys: From Binary Polycrystalline Alloys to Metallic Glasses and High Entropy Alloys

Abstract: Some of the factors responsible for good corrosion resistance of select polycrystalline and emerging alloys in chloride solutions are discussed with a goal of providing some perspectives on the current status and future directions. Traditional metallic glass alloys, single phase high entropy alloys (HEAs), early metallic glasses, and high entropy metallic glasses are all emerging corrosion-resistant alloys (CRAs) that utilize traditional strategies for improved corrosion resistance as well as take advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 120 publications
0
11
0
Order By: Relevance
“…2 By now it has been found that this is probably not the case and many of the alloys do not represent their thermodynamic ground state, but are rather kinetically inhibited from phase decomposition and do so upon annealing. 1,5,6 Thus, in this paper, we understand the term HEA not just as entropymaximizing alloys with equiatomic composition, but rather in the modern sense of multiprincipal-element alloys (MPEA) where concentrations do not need to be equiatomic 3,[7][8][9][10][11] . Their oxide equivalents, either high-entropy ceramics 12 or perovskite oxides 13 , are also a currently very actively researched field.…”
Section: Introductionmentioning
confidence: 99%
“…2 By now it has been found that this is probably not the case and many of the alloys do not represent their thermodynamic ground state, but are rather kinetically inhibited from phase decomposition and do so upon annealing. 1,5,6 Thus, in this paper, we understand the term HEA not just as entropymaximizing alloys with equiatomic composition, but rather in the modern sense of multiprincipal-element alloys (MPEA) where concentrations do not need to be equiatomic 3,[7][8][9][10][11] . Their oxide equivalents, either high-entropy ceramics 12 or perovskite oxides 13 , are also a currently very actively researched field.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to stainless steel, the passivity of such alloys are attributed to Cr 2 O 3 ‐rich passive film formed on the surface. [ 39 ] However, understanding the role of secondary alloying elements Mo and Fe on Cr‐based passivity was inadequate without the real‐time dissolution analysis. As indicated by the ASEC‐PDP curve (Figure 5b), both the oxidation rate and dissolution rate of Ni‐22Cr were significantly lower than that of pure Ni in 2 M H 2 SO 4 , reflecting the improved passivity due to Cr alloying.…”
Section: Corrosion Case Studiesmentioning
confidence: 99%
“…Ternary CoCrNi MEA shows better mechanical properties at low temperatures than some typical HEAs and most phase alloys (Gerard et al, 2020;Yeh et al, 2004). In the future, it will be a new type of high-performance structural material, making it have broad potential application prospects (Shin et al, 2014;Yoo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%